"Grzechy powszednie i śmiertelne", czyli Oriana Fallaci za kulisami Hollywood i Cinecitta = "Venial and mortal sins", or Oriana Fallaci behind the closed doors of Hollywood and Cinecitta - Tichoniuk-Wawrowicz, Ewa (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Oriana Fallaci became a journalist at 16 and a half years of age. Therefore, after a dozen or so years in the profession, this hard-working and brave author, despite her still young age, was recognized as a star herself. She spoke with many representatives of show business: Italian, French and American celebrities such as Federico Fellini, Arletty, Jeanne Moreau, Alfred Hitchcock or Paul Newman.
Keywords: Fallaci, Oriana (1929-2006); cinema; sins; interview; show business; kino; wywiad; grzech